Bovine adipose tissue derived stem cells bioengineering: isolation, characterization and differentiation studies - Fhataheya Buang (School of Bioprocess Engineering, 2013)
In this research, the objectives were 1) to identify isolation process of mesenchymal stem cells (MSCs) from bovine adipose tissue. 2) to characterize the isolated bovine ASCs and differentiated osteoblast cells. 3) to study the in vitro differentiation of bovine ASCs into osteogenic lineage 4) to compare cell growth in static culture (2D) and suspension 50ml culture (3D) of bovine ASCs